Architecture filmmaking - Troiani, Igea; Campbell, Hugh (Intellect Books Ltd, 2020)
This book investigates the ways in which architectural researchers, teachers of architecture, their students and practicing architects, filmmakers and artists are using filmmaking uniquely in their practice.